PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN KOMPETENSI TERHADAP KINERJA PEGAWAI KEMENTERIAN AGRARIA DAN TATA RUANG / BPN KANTOR PERTANAHAN KOTA PALEMBANG - Eggy Girniawan; Badia Perizade; Bambang Bemby Subiyakto; Bernadette Robbiani (Program Studi Magister Manajemen FE Unsri, 2019)
Tujuan penelitian– This research are to find out and to proof 1) The influence of Leadership, Organisation Culture & Competency simultaneously toward the employee performance of the ministry of agrarian affairs and spatial planning / BPN Land Agency Office Palembang. 2) The Influence of leadership toward the employee performance of the ministry of agrarian affairs and spatial planning / BPN Land Agency Office Palembang. 3) The influence of Organisation Culture toward the employee performance of the ministry of agrarian affairs and spatial planning / BPN Land Agency Office Palembang. 4) The influence of competency toward the employee performance of the ministry of agrarian affairs and spatial planning / BPN Land Agency Office Palembang.Desain/Metodologi/Pendekatan– To consider the total of the population is only 131 employees, the respondent took all the population but the head office and the researcher, therefore the writer used saturation sampling from 131 people in population, used as the instrument tester and used as a census to get the research data.Temuan– These three independent variables that are Leadership (X1), Organisation Culture (X2) and Competency (X3), partially has significant positive influence the employee performance of the ministry of agrarian affairs and spatial planning / BPN Land Agency Office Palembang (Y).Keterbatasan penelitian– The population of this research is the whole employee of the ministry of agrarian affairs and spatial planning /BPN Land Agency Office Palembang, 131 employee in total, consist of civilian state apparatus and non civilian state apparatus.Originality/value–Keywords: Leadership, Organisation Culture, Competency